FULL MOUNTH REHABILITATION WITH INNO IMPLANTS FAST AND FIXED SUPPORTED PROTHESE THROUGH THE ALL-ON-SIX AND ALL-ON- FOUR TECHNINIQUE - Mitrea Mihaela; Florea Claudia; Eldlbi Al Hage Walid; Raluca Jipu; Niculescu Simona (Romanian Society of Oral Rehabilitation, 2020)
Nowadays, total edentation is a global health problem, can be result of many factors such as poor oral hygiene, dental caries and periodontal disease. The edentulous condition has beeen shown to have a negative impact on oral health-related quality of life. The all-on-four treatment concept at mandible provides patients with an immediately loaded fixed prosthesis supported by 4 implants and the all-on-six treatment concept at jaw also. A number of ten patients were treated between august 2019 and September 2019 with immediate fast and fixed INNO implants, of which five needed bone addition and bilateral sinus lift. In the other five cases, reconstruction of the jaw and mandibular arch were performed using the all-on-four and all-on-six techniques. Correct diagnosis and accurate implant planning are key for success in implant rehabilitation. Accurate impressions and meticulous attention to detail provide a foundation for successful implant prosthodontics.